Photochemical Stability of a Cotton Fabric Surface Dyed with a Reactive Triphenodioxazine Dye - Liliana Rosu (MDPI AG, 2021)
The paper describes the photochemical stability of a commercial triphenodioxazine dye (Reactive Blue_204) linked onto a cotton fabric. Preliminary studies have shown that as a result of irradiation, the dye and its photodegradation products can pass directly onto the skin under conditions that mimic human perspiration and cause side-effects. The cotton dyed fabric was photo irradiated at different time intervals. Standard methods were employed to evaluate the color strength at various levels of pH, temperature, dyeing contact time, and salt concentration. The influence of UV radiation at different doses (λ > 300 nm) on the structural and color modifications of the dyed cotton fabrics was studied. Structural modifications before and after irradiation were compared by applying FTIR, UV–Vis, and near infrared chemical imaging (NIR–CI) techniques. Color modifications were investigated with the CIELAB system. Color differences significantly increased with the irradiation dose. High irradiation doses caused changes in the dye structure.